The concept of political authority in al-Mawardi and al-Farabi - Caksu, Ali (International Institute of Islamic Thought and Civilization (ISTAC), 1993)
As some events such as corruption and abuse of pcver which take place in most of the countries (including most of the socalled developed ones) show, the question of authority, its source, legitimization and control remain unsolved. Islamic societies are not free from this problem, and a confusion prevails all over the Islamic world. In this study I would like to elaborate on the concept of authority in Islam, and relevant questions such as its delegation, content, extent, application, manifestation and implications. However as this is a vast area and since there are several approaches by various schools, we shall restrict ourselves with two schools which developed more comprehensive and clearer political systems. These two approaches namely the juridical and the philosophical will be represented by al-Mawardi and al-Farabi respectively. The reason for my selection of these two scholars is as follows: Al-Mawardi (974-1058), the near contemporary of al-Baqillani and al-Baghdadi was a more important figure in the development of the juristic theory. Kis Ahkam al-Sultaniya is a key document for the theory of rule which came to be accepted by the jurists of the fifth century and after. Little advance was made on it by later theorists.1 "it has been generally accepted as the most 1Ann K.S Lambton, State and Government in Medieval Islam, Oxford University Press, New York 1985, p. 83. 2 authoritative exposition of uhe Sunni Islamic political theory"2. It is "the first comprehensive and systematic treatment of the Islamic system of government known as siyasa sharciyya {government in accordance with the revealed Law)".3 As for al-Farabi, his place in the Islamic philosophy is unquestionable. He was "one of the most eminent philosophers of the first formative centuries of Islamic thought".4 He constructed "an elaborate metaphysical system of great complexity". 5 "He was more than a pioneer" and profoundly influenced all subsequent Muslim philosophers, in particular Ibn Bajja and Ibn Rushd in Spain, and Ibn Sina in the East".6 In the Introduction I shall give a brief analysis of the concept of authority and some relevant concepts such as power and legitimacy as they are used in the present day literature, and later clarify in what sense I employ them. In Chapter I and II, we will discuss the meanings of our key concepts linguistically, and then textually, that is, as they are exploited by the two authors. Chapter III and IV will deal with the elaboration of the doctrines of our authors, and the place of the concept of authority in each of them.